Presentation of the first international research network to foster high-quality clinical trials testing non-pharmacological interventions (TRACTION network) - Ferreira, Ricardo J.O. (2024)
Funding Information: This paper is disseminated as part of the TRACTION project. TRACTION has received funding from the EEA Grants under the Bilateral Relations Fund (FBR_OC2_33). The REMEDY Center was funded by the Research Council of Norway, grant number 328657. Publisher Copyright: © Author(s) (or their employer(s)) 2024. Re-use permitted under CC BY. Published by BMJ.